Green Chemistry Integrated Teaching Module Design To Optimize High School Students Critical Thinking Skills (Study On The Main Topic Of Acid and based) - Halisah, Nur; Jusniar, Jusniar; Auliah, Army (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
This development research aims to produce a valid and practical integrated green chemistry teaching module using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The instrument used to measure validity is the validation sheet. The instrument for practicality is the observation sheet of lesson implementation and the teacher and student perception questionnaires. The research was conducted at SMAN 8 Makassar in August 2024. The results of the module's validity obtained a very valid average score of 3.70 with a consistency between rates of 1.00. The practicality of the module based on lesson implementation was 99.21%. The positive perceptions of teachers and students were 93.18% and 93.83%, respectively, both in the very practical category. The conclusion drawn is that the developed integrated green chemistry teaching module meets the validity and practicality criteria for use in teaching.